A GROUNDED THEORY APPROACH TO THE CRITICAL THINKING TENDENCIES OF STUDENTS WITH DISABILITIES IN MATHEMATICS LESSONS - Jaya, Daniel Jesayanto; Mara, Andry Ananda Putra Tanggu; Murtinugraha, R. Eka; Handoyo, Santoso Sri; Ramadhan, M Agphin; Subiyantari, Ansheila Rusyda; Anisah; Arifah, Shilmi; Abd Majid, Mohamad Zuber (Jurusan Pendidikan Luar Biasa, 2025)
This study analyzes the critical thinking tendencies of students with physical disabilities in mathematics learning at SMA-LB Negeri 3 Yogyakarta using a Grounded Theory approach. A qualitative method was applied, with data collected through observations, interviews, and questionnaires. The results indicate that 80% of students exhibit positive critical thinking tendencies, while 20% face internal challenges such as shyness, lack of confidence, and difficulty in collaboration. The main factors influencing critical thinking tendencies include the role of teachers, student participation, and classroom conditions. Teachers who implement interactive learning strategies, such as discussions and cooperative learning, play a crucial role in motivating students. A comfortable learning environment and adequate facilities also support the development of students' critical thinking skills. This study concludes that interactive teaching strategies and a conducive learning atmosphere are key to fostering students' critical thinking tendencies.